Forest Management, Engineering, and Operations / Global Competency and Issues in Contemporary Education - Finto Antony; Lewis Jordan; Laurie Schimleck; Richard Daniels; Rapeepan Kantavichai; Lara Hansen; Jessica Hitt; William Hubbard; Gwendolyn Boyd; Ryan Boyles; Heather Dinon; Joshua Idassi; et al. (Journal of Forestry, 2011)
31Maps depicting spatial variation in wood properties are important for forest product industries as they aid decision making regarding raw material procurement, can assist in product categorization and help improve utilization. Loblolly pine is an important commercial species grown throughout the southern Unites States of America (USA). Wood Quality Consortium (WQC)—a joint collaboration between the University of Georgia, USDA Forest Service and industries—was established in 1999 with the objective of characterizing wood property variation of plantation grown loblolly pine. Data on wood specific gravity (SG), modulus of elasticity (MOE) and modulus of rupture (MOR) collected by the WQC was utilized in this study. Maps showing spatial variation in SG at different stand ages and SG, MOE and MOR at different heights within a tree were developed using appropriate spatial prediction methods (kriging). The geographical variation of these wood properties across southeastern USA was demonstrated here.